THE IMPLEMENTATION OF PROJECT BASED LEARNING IN TEACHING ENGLISH - Fitriyani, Fitriyani (Bulletin of Scientific Reseach in English Education, 2024)
Project-based learning is a type of learning model in which students learn something by completing a project developed by the teacher. This study aims to find out how is the implementation of project-based learning in teaching English and how is the teacher’s perspective of the implementation project-based learning in teaching English. The descriptive qualitative research design was used in this study. The study was carried out in the eighth grade at SMP Nurul Fajri. This study used observation checklist, interview sheet and document analyses to obtain the data. The findings from this study showed that the teacher has not implemented the project-based learning optimally. It was discovered that implementing project-based learning had significant benefits for students. Furthermore, the teacher effectively used scientific ideas that transformed the teaching and learning process from traditional teacher-centered to student-centered.